2015
DOI: 10.3892/ol.2015.3728
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of cell cycle regulator genes CCND1 G870A and TP53 C215G: Association with colorectal cancer susceptibility risk in a Malaysian population

Abstract: Abstract. Colorectal cancer (CRC) occurs as a more common sporadic form and a less common familial form. Our earlier analysis of germline mutations of mismatch repair genes confirmed only 32% of familial CRC cases as Lynch syndrome cases. It was hypothesized that the remaining familial aggregation may be 'polygenic' due to single nucleotide polymorphisms (SNPs) of low penetrance genes involved in cancer predisposition pathways, such as cell cycle regulation and apoptosis pathways. The current case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…High activity of CCND1 is common in a lot of human tumors 47,48. Several case–control studies have reported a positive signal of the CCND1 rs9344 G>A polymorphism with the risk of CRC;1016 however, others have reported negative signal 17,18. Because of conflicting results and the insufficient sample size of individual studies, the final decision was far from certain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High activity of CCND1 is common in a lot of human tumors 47,48. Several case–control studies have reported a positive signal of the CCND1 rs9344 G>A polymorphism with the risk of CRC;1016 however, others have reported negative signal 17,18. Because of conflicting results and the insufficient sample size of individual studies, the final decision was far from certain.…”
Section: Discussionmentioning
confidence: 99%
“…Results of prior studies showed that the A allele of CCND1 rs9344 G>A resulted in an increasing level of mRNA (transcript-b) encoding CCND1 protein with an altered C-terminal domain 8,9. Results of some epidemiologic studies demonstrated that CCND1 rs9344 G>A polymorphism might confer CRC risk 1018. Several meta-analyses showed that CCND1 rs9344 G>A polymorphism might be a risk factor for CRC, especially in the subgroups of sCRC and Caucasians 1921.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported an association of people with a Pro allele in their TP53 Arg72Pro (rs1042522) polymorphism with a decreased risk of sporadic CRC [31, 32, 33]. However, a case–control study reported no association of the TP53 polymorphism with CRC in patients with Lynch syndrome [34].…”
Section: Discussionmentioning
confidence: 99%